COMMUNICATIVELY ORIENTED TEACHING OF GRAMMAR - Abduvokhidova Shakhribonu Akmalovna (Galaxy International Interdisciplinary Research Journal, 2022)
Nowadays, the problem of developing creative abilities in adolescents is especially relevant in the process of teaching English. In the modern context of the pedagogical process of secondary schools, this is an important scientific problem of historical, ethnic, cultural and socio-pedagogical significance.The development of creative abilities of school students is not possible without generalizing the experience of using English lessons in the system of education and upbringing. The study of English, its history of development, folk culture and daily life is one of the conditions not only for students to learn English, but also for teaching a foreign language and developing the creative abilities of schoolchildren on specific life material should be considered as.